2012
DOI: 10.4067/s0718-95162012005000022
|View full text |Cite
|
Sign up to set email alerts
|

Carbon stock and mineral factors controlling soil organic carbon in a climatic gradient, Golestan province

Abstract: Organic matter content of the many soils is less than 5% by weight; nevertheless this small amount of organic matter (OM) has a significant impact on soil properties. A study to evaluate the role of climate in distribution of organic carbon (OC) and mineral factors (such as soil composition, soil stability and clay minerals) controlling OC was performed. Seven surface soils were collected (0-20 cm depth) with three replications in a climate gradient (200 to 800 mm of rainfall). The results showed that aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
(32 reference statements)
2
21
0
Order By: Relevance
“…In contrast, CEC was primarily associated with OC content in Spain, as has been seen in other studies (Khaledian et Khaledian et al Catena 158 (2017) 194-200 different results were observed in this study in the agriculture, forest and Iran categories. These results indicated that soil CEC was more strongly controlled by clay than soil OC, as described by Zeraatpishe and Khormali (2012). The different behavior of the soils in Spain might due to the changes in soil properties triggered by long-term intensive agriculture, which changed the soil properties due to ploughing and the use of pesticides.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In contrast, CEC was primarily associated with OC content in Spain, as has been seen in other studies (Khaledian et Khaledian et al Catena 158 (2017) 194-200 different results were observed in this study in the agriculture, forest and Iran categories. These results indicated that soil CEC was more strongly controlled by clay than soil OC, as described by Zeraatpishe and Khormali (2012). The different behavior of the soils in Spain might due to the changes in soil properties triggered by long-term intensive agriculture, which changed the soil properties due to ploughing and the use of pesticides.…”
Section: Discussionmentioning
confidence: 64%
“…Ghorbani et al (2015) concluded that silt has less impact on the estimation of soil CEC than clay and sand. High amounts of OC can affect soil pH and, therefore, CEC (Zeraatpishe and Khormali, 2012). In addition, SOM, which is strongly correlated to OC, has a high CEC per unit volume (Brady and Weil, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that the use of plants and straw influences the biological dynamics of soil (Franchini et al, 2007), with positive effects on overall fertility, especially in levels of soil organic matter after a few years (Maia et al, 2013). The application of organic matter to the soil over time, improves the physical and chemical conditions, specific surface area, soil stability (aggregate size) and soil organisms (Zeraatpishe and Khormali, 2012;Khaledian et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, at the rural e-waste site there was a negative correlations between the PM and OC concentrations (r = -0.331, p = 0.010), but the EC contents varied less with PM (p = 0.755). This implied that the increase of PM in the rural air could be contributed largely by mineral particles from soils, which usually have lower organic matter content (less than 5%) (Zeraatpishe and Khormali, 2012). Alternatively, this could also be attributed to the low OC content particles released from e-waste recycling or to secondary inorganic ions that have been found to be significant components of PM.…”
Section: Characteristics Of Pmmentioning
confidence: 99%